The role of neutral Rh(PONOP)H, free NMe2H, boronium and ammonium salts in the dehydrocoupling of dimethylamine-borane using the cationic pincer [Rh(PONOP)(η2-H2)]+ catalyst. Issue 39 (20th September 2019) - Spearing-Ewyn, E. Anastasia K.; Beattie, Nicholas A.; Colebatch, Annie L.; Martinez-Martinez, Antonio J.; Docker, Andrew; Boyd, Timothy M.; Baillie, Gregg; Reed, Rachel; Macgregor, Stuart A.; Weller, Andrew S.
Abstract : Cationic σ-dihydrogen, σ-amine-borane and neutral hydride complexes, based upon Rh(PONOP), are all shown play a role in the dehydrocoupling of H3 B·NMe2 H. Movement between the three is promoted by free amine, NMe2 H. Abstract : The σ-amine-borane pincer complex [Rh(PONOP)(η 1 -H3 B·NMe3 )][BAr F 4 ] [2, PONOP = κ 3 -NC5 H3 -2, 6-(OP t Bu2 )2 ] is prepared by addition of H3 B·NMe3 to the dihydrogen precursor [Rh(PONOP)(η 2 -H2 )][BAr F 4 ], 1 . In a similar way the related H3 B·NMe2 H complex [Rh(PONOP)(η 1 -H3 B·NMe2 H)][BAr F 4 ], 3, can be made in situ, but this undergoes dehydrocoupling to reform 1 and give the aminoborane dimer [H2 BNMe2 ]2 . NMR studies on this system reveal an intermediate neutral hydride forms, Rh(PONOP)H, 4, that has been prepared independently. 1 is a competent catalyst (2 mol%, ∼30 min) for the dehydrocoupling of H3 B·Me2 H. Kinetic, mechanistic and computational studies point to the role of NMe2 H in both forming the neutral hydride, via deprotonation of a σ-amine-borane complex and formation of aminoborane, and closing the catalytic cycle by reprotonation of the hydride by the thus-formed dimethyl ammonium [NMe2 H2 ] + . Competitive processes involving the generation of boronium [H2 B(NMe2 H)2 ] + are also discussed, but shown to be higher in energy. Off-cycle adducts between [NMe2 H2 ] + or [H2 B(NMe2 H)2 ] + and amine-boranes are also discussed that act to modify the kinetics of dehydrocoupling.